Upaya Meningkatkan Hasil Belajar Ketrampilan Lari Jarak Pendek Melalui Permainan Estafet Cone - Ananda Ryan Romadhon; Mochammad Ridwan; Muhammad Bambang Herinanta (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study employed the Classroom Action Research (CAR) method with the goal of enhancing short-distance running skills among students in class X TAV 1 at SMK Negeri 3 Surabaya by utilizing cone relay games. This approach was chosen due to the currently low outcomes in students' short-distance running skills. Observations revealed that these low outcomes are due to several factors, including teaching methods that lack creativity and innovation, which diminish students' interest in short-distance running. The teacher's role is essential as a facilitator to guide and improve students' movement skills. An effective approach is to introduce creative, innovative, and enjoyable games. The research showed that implementing the cone relay game fostered a fun and interactive learning environment, leading to increased student engagement. Results indicated an improvement in students' performance across cycles: initially, only 17 students (47%) met the minimum criteria, but this number rose to 26 students (72%) in cycle I and 31 students (86%) in cycle II. Therefore, it can be concluded that using cone relay games significantly enhances students' short-distance running skills.